Exploring the research landscape of COVID-19-induced olfactory dysfunction: A bibliometric study - Yang, Zhirong; Ma, Yukun; Bi, Wei; Tang, Jingqian (Frontiers in Neuroscience, 2023)
Since the outbreak of COVID-19, olfactory dysfunction (OD) has become an important and persistent legacy problem that seriously affects the quality of life. The purpose of this paper is to quantitatively analyze and visualize the current research status and development trend of COVID-19 related OD by using VOSviewer software. Based on the Web of Science database, a total of 1592 relevant documents were retrieved in January 2023, with publication time spanning from 2020 to 2023. The bibliometric analysis revealed that the most influential research results in the field of COVID-19 related OD were concentrated in journals of related disciplines such as otorhinolaryngology, medicine, general & internal, virology, neurosciences, etc. The knowledge base of the research is mainly formed in two fields: COVID-19 clinical research and OD specialized research. The research hotspots are mainly concentrated in six directions: COVID-19, long COVID, smell, anosmia, olfactory dysfunction, and recovery. Based on the results of the bibliometric analysis, the temporal trends of COVID-19 related OD studies were visually revealed, and relevant suggestions for future research were proposed.